2020
DOI: 10.2147/cmar.s279096
|View full text |Cite
|
Sign up to set email alerts
|

<p>Whole-Brain Radiotherapy Can Improve the Survival of Patients with Multiple Brain Metastases from Non-Small Cell Lung Cancer Treated by Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitors</p>

Abstract: To observe whether whole-brain radiotherapy (WBRT) can bring survival benefits to patients with multiple brain metastases (BM) from non-small cell lung cancer (NSCLC) treated by epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) and determine the best time for WBRT intervention. Methods: A retrospective analysis was performed on 148 patients diagnosed with EGFR gene-mutated NSCLC. All patients had multiple BM and received EGFR-TKI targeted therapy, which was performed to observe whether WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Additionally, when compared to EGFR-TKIs alone, concurrent EGFR-TKIs with WBRT enhanced median iPFS in patients with more than three BMs (P=0.001); however, there was no significant difference in median iPFS between the two treatment regimens in patients with three or fewer BMs (P=0.526). Slightly different from the results of the He ZY's (56) study, Chen C et al (57) observed that EGFR-TKIs combination with WBRT improved both iPFS (11.9 vs 10.2 months, p=0.039) and OS (21.0 vs 16.7 months, p=0.043) in NSCLC patients with EGFR mutations and BMs compared with just -TKIs. While the foregoing findings are intriguing, they are retrospective and need be further explored and confirmed in large-scale prospective clinical trials.…”
Section: Brain Metastasismentioning
confidence: 58%
See 1 more Smart Citation
“…Additionally, when compared to EGFR-TKIs alone, concurrent EGFR-TKIs with WBRT enhanced median iPFS in patients with more than three BMs (P=0.001); however, there was no significant difference in median iPFS between the two treatment regimens in patients with three or fewer BMs (P=0.526). Slightly different from the results of the He ZY's (56) study, Chen C et al (57) observed that EGFR-TKIs combination with WBRT improved both iPFS (11.9 vs 10.2 months, p=0.039) and OS (21.0 vs 16.7 months, p=0.043) in NSCLC patients with EGFR mutations and BMs compared with just -TKIs. While the foregoing findings are intriguing, they are retrospective and need be further explored and confirmed in large-scale prospective clinical trials.…”
Section: Brain Metastasismentioning
confidence: 58%
“…Contrary to the above researches's results, Liu S et al ( 77) discovered that the timing of brain radiotherapy has no influence on OS for EGFR-mutant NSCLC patients who have asymptomatic BMs. The research of Chen C et al (57) has the same result as that of Liu S et al ( 77) nevertheless, they found that compared with patients in the latter radiotherapy, the iPFS and OS tend to be prolonged in patients who were treated with WBRT whether upfront or concurrent EGFR-TKIs, but there was no statistical difference in the result. Therefore, prospective researches into the best method for patients with EGFR-mutant NSCLC who have BMs is crucial, with a focus on the timing of local therapies and the amount of BMs.…”
Section: Brain Metastasismentioning
confidence: 64%
“…Three observational studies found that median CNS-PFS was longer in patients who had received earlier or upfront versus no or delayed radiotherapy [ 32 , 68 , 88 ]. Additional observational studies found that EGFR TKIs in combination or sequenced with radiotherapy (WBRT and/or SRS) had longer median CNS-PFS than with EGFR TKI monotherapy [ 24 , 27 , 30 , 34 , 38 , 82 , 98 ]. Several of these combination studies were utilizing first- or second-generation EGFR TKIs.…”
Section: Resultsmentioning
confidence: 99%